Validation of Control of Course and Depth of Biomimetic Underwater Vehicle With Two Side and Two Tail Fins - Przybylski Michał (Polish Maritime Research)
Underwater vehicles that mimic the movements of marine animals have gained popularity in recent years due to their potential for increased manoeuvrability and efficiency. However, optimising the control systems of these vehicles for various underwater conditions remains a significant challenge due to their unconventional propulsion systems. This study is focused on the control of the course and depth of the mini CyberSeal, i.e. a biomimetic underwater vehicle equipped with two side and two tail fins. A key contribution of this research is the mathematical model of the hydrodynamic forces generated by the biomimetic propulsion system. These forces have been measured experimentally at various oscillation frequencies and fin deflections, accurately representing the propulsion dynamics for simulation and control design. Two different control strategies were implemented to achieve effective manoeuvrability: a proportional, integral, and derivative (PID) controller and a sliding mode controller (SMC). These controllers were designed to regulate the vehicle’s depth and course, and their parameters were selected based on simulation results. The control strategies were verified by a comparative analysis of simulation and experimental results. The results indicate that the proposed mathematical model is sufficient to tune the controller based on the simulation, and the experimental data confirm effective depth and course control.